The Relationship Among Mentalization, Mindfulness, Working Memory, and Schizotypal Personality Traits in the General Population - Török, Edina; Kéri, Szabolcs (Frontiers in Psychology, 2022)
Individuals with high schizotypal traits are less able to observe, describe, and monitor inner feelings, thoughts, and experiences, commonly referred to as mindfulness and mentalization. High schizotypy is also associated with impaired working memory. However, the relationship among mindfulness, mentalization, working memory, and schizotypal traits is unknown. Three hundred individuals from the community (mean age: 38.0 years, SD = 10.5; 49.3% women) completed questionnaires examining schizotypal traits, mindfulness, and mentalization and performed working memory tasks. Results revealed that mentalization was a general predictor of schizotypal traits, including unusual experiences, cognitive disorganization, introverted anhedonia, and impulsive nonconformity, when the effect of mindfulness and working memory was controlled. We also found a positive correlation between mindfulness and mentalization. Low mindfulness and mentalization performances were associated with high schizotypy. However, poor working memory was only weakly linked to cognitive disorganization and introverted anhedonia. These findings suggest that weak mentalization is a core feature of schizotypy independent of mindfulness and working memory.